Перспективы развития системы медицинской реабилитации в Украине - Зинченко, Елена Константиновна (Факт, 2017)
В работе представлены основные вопросы организации реабилитационной помощи в Украине и пути ее реформирования в соответствии с современными Европейскими требованиями и стандартами по физической и реабилитационной медицине на примере создания кластерной системы реабилитации. Среди основных принципов реабилитации особое внимание уделено этапности применения мер реабилитации и роли физических факторов воздействия с целью увеличения эффективности проводимых лечебных и реабилитационных мероприятий.

The main questions on the organization of rehabilitation care in Ukraine and the ways of its reformation in accordance with modern European requirements and standards for physical and rehabilitation medicine are highlighted in the work by the example of creating a cluster rehabilitation system. Among the basic principles of rehabilitation, special attention is paid to the stage-by-stage application of rehabilitation methods and the role of physical factors of influence with a view to increasing the efficiency of the medical and rehabilitation measures.
Developments' perspectives of medical rehabilitation in Ukraine
Keywords: реабилитация; физические факторы; этапность; эффективность; кластеры; rehabilitation; physical factors; periodicity; efficiency; clusters